THE DEVELOPMENT OF E-MAGAZINE BASED ON CANVA TO INCREASE READING INTEREST AND LEARNING OUTCOMES - Yuliani Yuliani; Hasanuddin Hasanuddin; Sitti Rahma Yunus (Jurnal IPA Terpadu, 2024)
This research is an R&D (Research and Development) with ADDIE model. The research aims to determine the validity, effectiveness and practicality of the magazine. The subjects were a teacher and students at SMP Negeri 27 Makassar class VIII 11. The instrument was a reading interest questionnaire and a learning outcomes test in the form of multiple choice questions. The research instruments for measuring product practicality are teacher response questionnaires and student response questionnaires. The results of the e-magazine validity analysis obtained an average of 4.6 in the “valid” category. The results of analysis on the practicality of e-magazines by educators were 94.2% in the “very positive” category. The results of analysis on the practicality of e-magazines by students were 81.3% in the “very positive” category. The results of analysis on the effectiveness of e-magazines in increasing reading interest obtained an N-gain of 0.4 in the “medium” category. The results of analysis on the effectiveness of e-magazines in improving learning outcomes obtained an N-gain of 0.5 in the “medium” category. Based on the description, it can be concluded that the Canva-based e-magazine is valid, practical and effective for application to the topic of the Solar System.